Note Taking Strategy: Its effect on Reading Comprehension - Puji Siswanto (English Department - University of Sultan Ageng Tirtayasa, 2019)
The study reports the investigation of the effect of Note Taking strategy on reading comprehension at one of Public Vocational High Schools in Banten. The study employs true experimental design with pretest and post test control group design. The findings of the data analysis show that experimental group performed better on reading comprehension than control class. It is proven by the value of the mean of experimental class is 8.00. Meanwhile; the mean of control class is 6.95. The value of the group sig is 0.00 < 0.05, so the Null hypothesis is rejected. It indicates that the Note Taking is greatly affected on reading comprehension. Meanwhile, the value of sex sig is 0.096 > 0.05 means that the null hypothesis is accepted. This means that there is not different of male and female who were taught by using Note Taking Strategy and those who were not taught by using Note Taking Strategy on their reading comprehension achievement.